Flexural behaviour of irregular flat plate floors - Khoh, Tio Ching. (2009)
The flexural behaviour of reinforced concrete flat plates with irregular column layout was analyzed by using elastic finite element analysis. Two sets of specimens, S7C and Manchester Slabs, were selected for this study. The effect of reinforcement’s direction and torsional moments on moment capacities of flat plates were investigated. The results showed that there is a good correlation among experimental moments, design moment capacities and calculated moments. A systematic method to design reinforced concrete flat plates with irregular column layout was proposed in this report.